Properties and hemispheric differences of theta oscillations in the human hippocampus. Issue 5 (1st March 2022) - Penner, Cooper; Minxha, Juri; Chandravadia, Nand; Mamelak, Adam N.; Rutishauser, Ueli
Abstract: The left and right primate hippocampi (LH and RH) are thought to support distinct functions, but little is known about differences between the hemispheres at the neuronal level. We recorded single‐neuron and local field potentials from the human hippocampus in epilepsy patients implanted with depth electrodes. We detected theta‐frequency bouts of oscillatory activity while patients performed a visual recognition memory task. Theta appeared in bouts of 3.16 cycles, with sawtooth‐shaped oscillations that had a prolonged downswing period. Outside the seizure onset zone, the average frequency of theta bouts was higher in the RH compared to the LH (6.0 vs. 5.3 Hz). LH theta bouts had lower amplitudes and a higher prevalence compared to the RH (26% vs. 21% of total time). Additionally, the RH contained a population of thin spiking visually tuned neurons that were not present in the LH. These data show that human theta appears in short oscillatory bouts whose properties vary between hemispheres, thereby revealing neurophysiological properties of the hippocampus that differ between the hemispheres.